ANALYSIS OF STUDENT'S HIGH-ORDER THINKING SKILLS IN STATISTICS METHOD COURSES IN THE ERA OF THE COVID-19 PANDEMIC - Payadnya, I Putu Ade Andre; Suwija, I Ketut (Universitas Papua, 2021)
Major changes in education caused by the Covid-19 Pandemic led to a decrease in students' thinking skills. Therefore, it is very important to analyze how the level of thinking ability of students in this era. The purpose of this study was to analyze students' higher order mathematical thinking skills in the era of Covid-19 Pandemic by using three stages of metaphorical thinking. This research was conducted in the even semester. The subjects in this study were 11 students of class IIB Mathematics Education Study Program, Universitas Mahasaraswati Denpasar. This research uses descriptive analysis techniques. Data collection was carried out through tests, interviews, observation, and documentation. The results showed that the students' high-order mathematical thinking skills were very low where only 20% of students answered correctly at the grounding metaphors stage, 25% at the linking metaphors stage, and only 25% at the redefinitional metaphors stage. In general, this phenomenon occurs due to the reduced opportunities for students to interact and discuss during online learning in the Pandemic era which also results in a lack of opportunities for students to exchange understanding and knowledge. Students also cannot understand problems in depth and relate concepts to everyday life.